Research and Clinical Progress of Therapeutic Tumor Vaccines - Chunyan Dong; Zhuang Li; Dejiang Tan; Huimin Sun; Jinghui Liang; Dexian Wei; Yiyang Zheng; Linyu Zhang; Sihan Liu; Yu Zhang; Junzhi Wang; Qing He (Vaccines)
Therapeutic cancer vaccines are a new growth point of biomedicine with broad industrial prospects in the post-COVID-19 era. Many large international pharmaceutical companies and emerging biotechnology companies are deploying different tumor therapeutic cancer vaccine projects, focusing on promoting their clinical transformation, and the vaccine industry has strong momentum for development. Such vaccines are also the core engine and pilot site for the development of new vaccine targets, new vectors, new adjuvants, and new technologies, which play a key role in promoting the innovation and development of vaccines. Various therapeutic cancer vaccines, such as viral vector vaccines, bacterial vector vaccines, cell vector vaccines, peptide vaccines, and nucleic acid vaccines, have all been applied in clinical research. With the continuous development of technology, therapeutic cancer vaccines are evolving towards the trends of precise antigens, efficient carriers, diversified adjuvants, and combined applications. For instance, the rapidly advancing mRNA-4157 vaccine is a typical representative that combines personalized antigens with efficient delivery vectors (lipid nanoparticles, LNPs), and it also shows synergistic advantages in melanoma patients treated in combination with immune checkpoint inhibitors. In this article, we will systematically discuss the current research and development status and clinical research progress of various therapeutic cancer vaccines.